2016
DOI: 10.1080/00140139.2016.1222001
|View full text |Cite
|
Sign up to set email alerts
|

Additional helmet and pack loading reduce situational awareness during the establishment of marksmanship posture

Abstract: The pickup of visual information is critical for controlling movement and maintaining situational awareness in dangerous situations. Altered coordination while wearing protective equipment may impact the likelihood of injury or death. This investigation examined the consequences of load magnitude and distribution on situational awareness, segmental coordination and head gaze in several protective equipment ensembles. Twelve soldiers stepped down onto force plates and were instructed to quickly and accurately i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The results showed trunk inclination values lower (i.e., more upright postures) than other team sports such as field hockey, in which the mean trunk inclination in match play was ~45° and little differences between the playing positions were observed (defenders: ~43.5°; midfielders: ~44.2°; strikers: ~46.4°) [ 10 ]. The trunk flexion position lets the players carry out soccer-specific movements (e.g., running, passing, or controlling the ball) but these actions may move the field of regard down and limit the visual exploration [ 10 , 16 ]. In addition, soccer is a team sport with continuous running actions, accelerations, decelerations, and changes of directions for each position [ 2 , 19 ], which induce constant trunk accelerations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed trunk inclination values lower (i.e., more upright postures) than other team sports such as field hockey, in which the mean trunk inclination in match play was ~45° and little differences between the playing positions were observed (defenders: ~43.5°; midfielders: ~44.2°; strikers: ~46.4°) [ 10 ]. The trunk flexion position lets the players carry out soccer-specific movements (e.g., running, passing, or controlling the ball) but these actions may move the field of regard down and limit the visual exploration [ 10 , 16 ]. In addition, soccer is a team sport with continuous running actions, accelerations, decelerations, and changes of directions for each position [ 2 , 19 ], which induce constant trunk accelerations.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the differences in the activity-profile from each position may explain why there were positional differences in G-forces in match play. In consequence, the development of position-specific training drills considering the trunk inclination and G-forces experienced by the players is necessary to prepare not only for the physical demands (e.g., training trunk flexion postures with constant G-forces, which may avoid low back pain) [ 12 ] but also for successful performance in the field of regard [ 10 , 16 ]. However, this consideration does not seem to be so important for the locomotor efficiency ratio since no positional differences were found, which confirms the results reported by a previous investigation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent investigation on field hockey players observed that these were half of a match in two trunk flexion zones (30°–40°: ~26% of total time and 40°–50°: ~26% of total time) [ 4 ]. This trunk inclination allowed the players to perform the sport-specific movements such as running with the ball or passing and controlling the ball, which may move the field of regard down [ 4 , 5 ]. In addition, the results showed that the playing position should be also considered when analyzing the postural demands.…”
Section: Discussionmentioning
confidence: 99%
“…Then, as in other team sports in which the ball, teammates, referees, or opposition players are continually in motion, it is suggested that the understanding of the postural demands met by the players when performing sports-specific skills would provide coaches and performance analysts with meaningful information about their performance in perception and action [ 4 ]. For example, the downward orientation of the head and the trunk may restrict the ability to perform in the field of regard [ 4 , 5 ]. However, soccer players usually play the ball with the feet, which may increase the trunk flexion and move the field of regard down [ 4 ].…”
Section: Introductionmentioning
confidence: 99%